On estimating the risk that shareholders bear during hostile merger activity - D. J. Bradfield; D. C. Bowie (South African Journal of Business Management, 1991)
In this article a model is proposed for measuring the risk that shareholders bear during hostile merger activities. An empirical study on the failed Minorco-Consolidated Goldfields merger attempt reveals several insights on the additional risk borne by Minorco and Consolidated Goldfields shareholders. Risk statistics computed using the proposed model reveal that shareholders of both companies were exposed to additional risk as a consequence of the hostility of the merger activities. The evidence shows that the proportion of risk attributable to the hostilities increased by a factor of approximately five for both bidding and defending companies.
Keywords: 650